2022
DOI: 10.1530/ec-21-0546
|View full text |Cite
|
Sign up to set email alerts
|

Insulin therapy and biliary tract cancer: insights from real-world data

Abstract: Objective: The association between insulin therapy and the risk of biliary tract cancer (BTC) is uncertain, we aimed to assess this risk in type 2 diabetic patients. Methods: Using electronic medical data from the Shanghai Hospital Link database, 202,557 patients with type 2 diabetes (164,997 insulin never-users and 37,560 insulin ever-users) were identified in this study between January 1, 2013, and December 31, 2016, with follow-up until December 31, 2019. By propensity score matching, an ever-user was matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…As high glucose levels promote cancer cell growth in vitro and in vivo 16 , 38 , the administration of liraglutide might control plasma glucose levels in the treated mice within relatively lower ranges than the control and then slow the tumor growth. In agreement with reports showing that insulin levels and GLP-1R agonists were not associated with increased risk of intrahepatic and perihilar CCA 21 23 , 31 , our previous study showed insulin did not enhance CCA cell proliferation in vitro 39 and suggests that using GLP-1R agonists in iCCA patients with DM might be safe. This study also demonstrated for the first time that liraglutide suppressed GLP-1R expression in iCCA cells, both in vitro and vivo and incorporated with suppression of iCCA cell migration and reduction of tumor growth in iCCA xenografts.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As high glucose levels promote cancer cell growth in vitro and in vivo 16 , 38 , the administration of liraglutide might control plasma glucose levels in the treated mice within relatively lower ranges than the control and then slow the tumor growth. In agreement with reports showing that insulin levels and GLP-1R agonists were not associated with increased risk of intrahepatic and perihilar CCA 21 23 , 31 , our previous study showed insulin did not enhance CCA cell proliferation in vitro 39 and suggests that using GLP-1R agonists in iCCA patients with DM might be safe. This study also demonstrated for the first time that liraglutide suppressed GLP-1R expression in iCCA cells, both in vitro and vivo and incorporated with suppression of iCCA cell migration and reduction of tumor growth in iCCA xenografts.…”
Section: Discussionsupporting
confidence: 92%
“…Associations between DM and CCA carcinogenesis and progression have been previously reported in several studies, both at the epidemiology and molecular levels 6,7,12,16,17,27 . The underlying mechanisms are known to involve the effects of hyperglycemia and probably the effects of hormonal disturbances 16,17,30,31 . Our previous reports demonstrated that high glucose level is a promoting factor for CCA via the activating effects on multiple signaling pathways [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Back in 2013, Schlesinger and colleagues attempted to assess the risk of BTC in diabetic patients treated with insulin, but they were unable to conclude because only two cases of BTC were observed in 2,156 insulin users [ 60 ]. To fill this knowledge gap in this area, we conducted a study in 2021 using electronic medical record data, which showed that insulin therapy was associated with an increased hazard ratio (HR) of ECC (HR, 4.10; 95% CI, 1.54–10.92) but not ICC (HR, 1.36; 95% CI, 0.30–6.09) or GBC (HR, 1.28; 95% CI, 0.61–2.66) (Table 1 ) [ 15 ]. However, only this study has yielded some statistically significant results, and due to residual confounding factors, it is still unable to draw definitive conclusions about the relationship between insulin and BTC.…”
Section: Insulin and Btc: Limited Evidence From Only One Cohort Studymentioning
confidence: 99%
“…Recently, some important findings related to insulin/incretin-based drugs and BTC have been reported, which provide new evidence for further study. A study from China showed that insulin was associated with an increased risk of ECC but not ICC or GBC [ 15 ], indicating a type-specific relationship between insulin and BTC. A comprehensive meta-analysis of randomized clinical trials showed that incretin-based drugs were not associated with an increased risk of BTC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%